2023
DOI: 10.3389/fped.2023.1101546
|View full text |Cite
|
Sign up to set email alerts
|

Inotropic score and vasoactive inotropic score as predictors of outcomes in congenital diaphragmatic hernia: A single center retrospective study

Abstract: BackgroundNeonates with congenital diaphragmatic hernia (CDH) have varying degrees of pulmonary hypoplasia, pulmonary hypertension (PH) and cardiac dysfunction. These neonates frequently require vasoactive support and are at high risk for mortality and morbidity, including prolonged ventilator support, need for extracorporeal membrane oxygenation (ECMO), prolonged length of stay, and need for tracheostomy. However, identifying which infants are at increased risk can be challenging. In this study, we sought to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Gopal et al evaluated the Inotropic Score (IS) and the VIS in a retrospective single-center cohort of 57 CDH infants. 8 In conclusion, the authors found the IS/VIS at 6 h of life to be independently associated with the clinical outcome (ECMO and ) as an appropriate independent risk factor for in-hospital mortality. The authors report an optimal cut-off of >17 for the hosVIS…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Gopal et al evaluated the Inotropic Score (IS) and the VIS in a retrospective single-center cohort of 57 CDH infants. 8 In conclusion, the authors found the IS/VIS at 6 h of life to be independently associated with the clinical outcome (ECMO and ) as an appropriate independent risk factor for in-hospital mortality. The authors report an optimal cut-off of >17 for the hosVIS…”
Section: Discussionmentioning
confidence: 79%
“…In two recently published studies, the VIS was evaluated in the CDH population. Gopal et al evaluated the Inotropic Score (IS) and the VIS in a retrospective single‐center cohort of 57 CDH infants 8 . In conclusion, the authors found the IS/VIS at 6 h of life to be independently associated with the clinical outcome (ECMO and death) and echocardiographic severity parameters of cardiac function, as atrial level shunting, interventricular septal flattening and bowing, and LV function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the cutoff values were derived from our study’s dataset, they may be broadly applicable, as most studies investigating fluid responsiveness have selected a fluid bolus dose of 10 ml/kg [ 6 ]. Regarding higher VIS, it has been reported that VIS > 5–10 is associated with postoperative outcomes [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%